Prevention of mother-to-child transmission of HIV/AIDS: Revitalization and organization of services in the provincial health division of Kwango, Democratic Republic of the Congo : Assessing the Performance of PMTCT Services in a Resource-Limited Setting - Kisaka, Ngimbi Jean Jacques; Mukandu , Baswa Babintu Leyka; Inipavudu, Baellani John; Tsikisa , Sibadiamambu Didier; Bipa , Kisita Espoir (Orapuh Journal, 2025)
Introduction Mother-to-child transmission (MTCT) of HIV remains a major public health concern in the Democratic Republic of the Congo, particularly in Kwango Province, where the organisation of prevention services is inadequate. Purpose This study aims to assess the organisation of HIV prevention of mother-to-child transmission (PMTCT) services within the Provincial Health Division of Kwango, with the goal of proposing revitalisation strategies tailored to the local context. Methods A cross-sectional descriptive study was conducted among 380 participants, including pregnant women, healthcare providers, and community actors. Sampling involved proportional stratification for pregnant women and purposive sampling for other stakeholders. Data were collected using structured questionnaires, semi-structured interviews, and direct observations. Statistical analyses (Chi²) were used to examine relationships between sociodemographic variables and the use of PMTCT services. Results Only 26.1% of respondents were aware of PMTCT, and over 70% perceived poor accessibility to the services. The availability of supplies, staff training, and community involvement were deemed insufficient. The main challenges identified included stock-outs, lack of intersectoral coordination, and stigma. Significant associations were observed between access to PMTCT services and factors such as age, education level, perception of accessibility, service availability, and community involvement. Conclusion The effectiveness of PMTCT services in Kwango Province is hindered by numerous organisational weaknesses. Service restructuring, capacity building for providers, greater community mobilisation, and improved coordination are essential to enhance the coverage and impact of HIV prevention interventions for mothers and children.